Open Repair of a Giant Popliteal Artery Aneurysm Presenting with Nerve Compression Symptoms - Masaya Nakashima; Masayoshi Kobayashi (Vascular Specialist International, 2021)
Popliteal artery aneurysm (PAA) is a rare vascular disease, especially in women, and presents with various symptoms, ranging from being asymptomatic to rupture or acute life-threatening ischemia. We have presented a case of PAA in an 81-yearold woman complaining of tingling sensations in her leg. Computed tomography revealed a large 10-cm sized PAA. Because of the compression related symptoms, an open repair approach was selected and performed successfully via a posterior approach, including partial aneurysm resection and interposition graft with a reversed saphenous vein.